Evolutionary innovation through fusion of sequences from across the tree of life - Rishabh R. Kapoor; Evelyn E. Schwager; Supanat Phuangphong; Emily L. Rivard; Chandrashekar Kuyyamudi; Suhrid Ghosh; Isobel Ronai; Cassandra G. Extavour (Proceedings of the National Academy of Sciences, 2026)
Novel genes arise through multiple mechanisms, including gene duplication, gene fusion, and horizontal gene transfer (HGT). While HGT has increasingly been documented in animals, the posttransfer evolutionary fate of horizontally acquired genes is less well understood. We hypothesized that fusion with endogenous sequences in animal genomes might generate what we call “HGT-chimeras”: genes with regions of nonmetazoan and metazoan descent in the same open reading frame. To test this hypothesis, we developed a molecular phylogenetics pipeline that enables the identification of HGT-chimeras. We applied our pipeline to 319 high-quality annotated arthropod genomes and uncovered a high-confidence set of 274 HGT-chimeras corresponding to 104 independent origination events across diverse arthropods. HGT-chimeras contain intervals acquired from across the tree of life, and many likely originated via a gene duplication-based mechanism. To assess whether HGT-chimeras might be functionally important, we performed RT-PCR and Sanger sequencing of tissues from 20 arthropod species predicted to harbor HGT-chimeras in their genome. We found evidence for the expression of contiguous chimeric messenger RNA transcripts (mRNAs) for 36 of 41 tested HGT-chimeras across 18 of 20 different tested species. We also found evidence that HGT-chimeras evolve under purifying selection and have acquired potentially functional domain architectures, consistent with the hypothesis that these genes are in active use and may participate in diverse biological processes. These results illuminate an underappreciated combinatorial mechanism underlying the origin of novel genes across the largest animal phylum, and suggest that interdomain sequence fusion can play important roles in animal biology and evolution.